Disease-associated human histocompatibility leukocyte antigen determinants in patients with seropositive rheumatoid arthritis. Functional role in antigen-specific and allogeneic T cell recognition. - Weyand, C M (1990)
The susceptibility to develop seropositive rheumatoid arthritis (RA) has been linked to specific genomic polymorphisms within the HLA complex. Two different haplotypes have been associated with the disease, HLA-DR1 and HLA-DR4. To investigate the link between such phenotypic disease associations and potential immune mechanisms we used alloreactive and antigen-specific human T cell clones. Here we describe a panel of alloreactive T cell clones directed to polymorphic determinants encoded by the third hypervariable region (hvr) of the HLA-DR beta 1-chain. T cell determinants defined by these clones are shared among HLA-DR1, HLA-Dw4, HLA-Dw13, HLA-Dw14, and HLA-Dw15, and are frequent in a population of RA patients. To study the role of such disease-associated epitopes in antigen-restricted T cell recognition we generated T cell clones from RA patients specific for mycobacterial antigens, Epstein-Barr virus antigens, and tetanus toxoid. In all three antigenic systems T cell clones were restricted to either HLA-DR1 or HLA-DR4. These data suggest that the polymorphisms within the first and second hvr of the HLA-DR beta 1-chain that are distinct in HLA-DR1 and HLA-DR4 and not associated with the disease are crucially involved in the recognition of antigens. Polymorphic determinants encoded by the third hvr are shared among disease-associated haplotypes and may function to mediate the interaction of alloreactive T cell receptor molecules with the HLA complex.